A Comparison of American and Nepalese Children's Concepts of Freedom of Choice and Social Constraint. (20th May 2013) - Chernyak, Nadia; Kushnir, Tamar; Sullivan, Katherine M.; Wang, Qi
Abstract: Recent work has shown that preschool‐aged children and adults understand freedom of choice regardless of culture, but that adults across cultures differ in perceiving social obligations as constraints on action. To investigate the development of these cultural differences and universalities, we interviewed school‐aged children (4–11) in Nepal and the United States regarding beliefs about people's freedom of choice and constraint to follow preferences, perform impossible acts, and break social obligations. Children across cultures and ages universally endorsed the choice to follow preferences but not to perform impossible acts. Age and culture effects also emerged: Young children in both cultures viewed social obligations as constraints on action, but American children did so less as they aged. These findings suggest that while basic notions of free choice are universal, recognitions of social obligations as constraints on action may be culturally learned.